Apple Surface Defect Detection Method Based on Weight Comparison Transfer Learning with MobileNetV3 - Si, Haiping (2023)
Si, H., Wang, Y., Zhao, W., Wang, M., Song, J., Wan, L., Song, Z., Li, Y., Bação, F., & Sun, C. (2023). Apple Surface Defect Detection Method Based on Weight Comparison Transfer Learning with MobileNetV3. Agriculture (Switzerland), 13(4), 1-26. [824]. https://doi.org/10.3390/agriculture13040824---This research is funded by the Henan Province Key Science-Technology Research Project under Grant No. 232102520006, the National Science and Technology Resource Sharing Service Platform Project under Grant No. NCGRC-2020-57.